A sensitive sandwich ELISA using a modified biotin-streptavidin amplified system for histamine detection in fish, prawn and crab. (15th July 2021) - Yang, Fanfan; Xu, Long; Dias, Alberto C.P.; Zhang, Xiaoying
Graphical abstract: Highlights: Long-armed biotin and biotinylated-polylysine-histamine complex were synthesized. A linear range of 11.7–1500 ng mL −1 with a LOD of 5.86 ng mL −1 was obtained. A sandwich ELISA for histamine detection in fish, prawn and crab was proposed. The developed assay was 15-fold more sensitive than previous ic-ELISA. Abstract: Histamine poisoning from seafood is a significant public health and safety concern. To detect histamine sensitively and accurately, a novel competitive sandwich immunoassay using a modified biotin-streptavidin system coupling with polylysine was developed. Using this strategy, a sandwich ELISA with an IC50 value of 112.8 ng mL −1 and a broad linear range of 11.7– 1500 ng mL −1 with a correlation coefficient of 0.9942 was validated. Without any sample derivatization procedure, the recovery of histamine ranged from 80.19% to 108.3% with a coefficient of variation of 1.43–11.7% in tuna, prawn and crab. The sandwich ELISA had a detection limit of 5.86 ng mL −1, which was 15-fold lower than an indirect competitive ELISA (ic-ELISA). This simple, sensitive and accurate method can be applied to detect histamine in routine seafood samples.